Analysis and construction of evaluation index system of inter-provincial electricity spot markets - Hao Yue; Yu Zhang; Jiahao Guo; Yang Hu; Chengmei Wei; Heping Jia; Dunnan Liu; Dunjian Xie (Global Energy Interconnection)
Because of the contradiction between the scale of new energy installations and the continuous load growth in the central and eastern regions of China, the balance problems of the electricity market are becoming increasingly prominent, and it is urgent to solve such problems through inter-provincial electricity spot markets. First, the development history and construction status of the inter-provincial electricity spot market are summarized; second, the mechanism design of the inter-provincial electricity spot market is sorted out in terms of the market operation framework, transaction declaration, and clearing methods; subsequently, the evaluation index system of the inter-provincial electricity spot market is constructed, including four themes of electricity mutual aid and support, new energy consumption, economic benefits of market-based allocation, and social benefits of market-based allocation; finally, the operation of the inter-provincial electricity spot market is comprehensively analyzed by the algorithm based on the market operation data of 2022, which proves the feasibility and practicality of the proposed index system.